Lipid droplet-associated proteins (LDAPs) are involved in the compartmentalization of lipophilic compounds in plant cells - Gidda, Satinder K (Landes Bioscience, 2013)
While lipid droplets have traditionally been considered as inert sites for the storage of triacylglycerols and sterol esters, they are now recognized as dynamic and functionally diverse organelles involved in energy homeostasis, lipid signaling, and stress responses. Unlike most other organelles, lipid droplets are delineated by a half-unit membrane whose protein constituents are poorly understood, except in the specialized case of oleosins, which are associated with seed lipid droplets. Recently, we identified a new class of lipid-droplet associated proteins called LDAPs that localize specifically to the lipid droplet surface within plant cells and share extensive sequence similarity with the small rubber particle proteins (SRPPs) found in rubber-accumulating plants. Here, we provide additional evidence for a role of LDAPs in lipid accumulation in oil-rich fruit tissues, and further explore the functional relationships between LDAPs and SRPPs. In addition, we propose that the larger LDAP/SRPP protein family plays important roles in the compartmentalization of lipophilic compounds, including triacylglycerols and polyisoprenoids, into lipid droplets within plant cells. Potential roles in lipid droplet biogenesis and function of these proteins also are discussed.